The Serious Labor Offense - Pasco Cosmópolis, Mario (1985)
This article deals with serious labor misconduct, a concept that justifies the termination of the employment contract. The author presents different systems of classification of misconduct, including enumerative, open and mixed systems, highlighting the importance of case law in the interpretation of labor laws. In addition, he addresses the types of serious misconduct and their impact on labor stability, such as unjustified failure to comply with obligations and decrease in quality or quantity of work. He also discusses dismissal as a sanction for serious misconduct, emphasizing that it must be deliberate and not automatic, complying with formal requirements. In addition, the regulation of serious misconduct in the Peruvian Law and the evolution of the regulation up to the Decree Law 22126 are discussed. Finally, the author points out that, despite the existence of a regulation, it is impossible to catalog all possible misconduct, which implies a risk of constant omission, so it is necessary to take into account the changing social criteria and moral principles to regulate its definition and application.